Neuroprotective effects of DAHP and Triptolide in Focal Cerebral Ischemia via Apoptosis Inhibition and PI3K/Akt/mTOR pathway Activation - Li, Weiyun; Yang, Yang; Hu, Zhiying; Ling, Shucai; Fang, Marong (Frontiers in Neuroanatomy, 2015)
Triptolide (TP), one of the major active components of the traditional Chinese herb Tripterygium wilfordii Hook F, and 2, 4-diamino-6-hydroxypyrimidine (DAHP), an inhibitor of tetrahydrobiopterin (BH4) synthesis, have been reported to have potent anti-inﬂammatory and immunosuppressive properties. However, the protective effects of TP and DAHP on cerebral ischemia have not been reported yet. In this study, we investigated the neuroprotective effects of TP and DAHP in a middle cerebral artery occlusion (MCAO) rat model. Furthermore, we examined whether the neuroprotective effects of TP and DAHP were associated with the inhibition of apoptosis through suppressing BH4 and inducible NOS (iNOS) synthesis or the activation of the phosphoinositide-3-kinase/serine-threonine kinase Akt/ mammalian target of rapamycin (PI3K/Akt/mTOR) pathway. Our results showed that pretreatments with Triptolide (0.2 mg/kg) and DAHP (0.5g/kg) significantly reduced ischemic lesion volume, water content and neuronal cell death compared with the vehicle MCAO rats. In addition, compared with the MCAO group, TP and DAHP pretreatment groups significantly reduced astrocyte numbers, caspase-3, cleaved caspase-3 and NF-κB up-regulation, while increased Bcl-2 expression. Moreover, protein expressions of PI3K, Akt and mTOR increased, while extracellular signal-regulated protein kinases 1 and 2 (ERK1and 2) phosphorylation decreased in both the TP-treated rats and DAHP-treated rats. These results demonstrate that TP and DAHP can decrease cell apoptosis in focal cerebral ischemia rat brains and that the mechanism may be related to the activation of the PI3K/Akt/mTOR pathway and inactivation of the ERK1/2 pathway. Thus our hypothesis was reached PI3K/Akt/mTOR and ERK1/2 pathways may provide distinct cellular targets for a new generation of therapeutic agents for the treatment of stroke, and TP and DAHP may be potential neuroprotective agents for cerebral ischemia/reperfusion injury.